Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. The availability of artificial intelligence applications in social studies curricula in basic education schools in the Sultanate of Oman Dr. Humaid Muslem Said Al-Saidi, Mr. Fahad Abdullah Mohammed Al-Balushi, Mr. Mohammed Said Mohammed Al-Kaabi 2. The narrative approach in teaching the tafsir course and its effectiveness in developing conceptual comprehension for third year middle school students Co-Prof. Abdullah Fahad Alsanawi 3. The effectiveness of a program that is based on (STEM) preface in developing of teaching performance skills for student teachers in Faculty of Education - Sana’a Mrs. Eman Yahya Ahmed Hamod Sharf Al-Deen 4. The Effectiveness of Program Based on Fractal Geometry in Developing Nanotechnology Concepts among Mathematics Students at Faculty of Education Lecturer Ibtesam Mohammed Ahmed Al- Kamel , Prof. Radman Mohamed Saeed 5. The Extent to Which Computational Thinking Skills Are Included in Programming Units within Digital Skills Courses for Primary Schools in Saudi Arabia Mrs. Fatimah Abdulaziz Al-Rasheed , Dr. Mai Fahid Al-Fahid 6. Know the effect of a program that was built on the strategy of the planning organizations in developing the grammatical skills of the Eighth grade students of basic education in Sana’a Mr. Ahmed Ali Abdullah 7. The impact of using the digital story strategy in the achievement of the history subject for the sixth grade students in Jordan Mrs. Rasha Mohammed Almherat , Co-Prof. Fawaz Hassan Shehadeh 8. Common Errors of Level Three Students’ Writing at the English Department, Faculty of Education, Sana’a University Co-Prof. Fazee Khalid Alezi Almuslimi